An Empirical Study on the Effects of Walking Time on Knee Joint Pain Based on Korea National Health and Nutrition Examination Survey Data - Kim, Kyeong-Rae; Park, Jae-Eun; Lim, So-Young; Kim, Ho; Lee, Kwang-Yeol; Jang, Il-Tae (Central Asian Journal of Medical Sciences, 2019)
Objectives: It is generally reported that walking has a positive effect on knee joint pain. However, since previous studies have focused on small patient data and simple average comparisons, we proceed with more sophisticated empirical research using public data. Since the knee joint pain itself can be considered very important in terms of preventative medicine, we analyze that use of big data to identify its effect on knee joint pain. Methods: The present study used a logistic regression analysis and analyzed the effect of walking time on knee joint pain in the activities of daily living based on data from the 6th 2013–2014 Korea National Health and Nutrition Examination Survey. Results: Smoking, Drinking and Sedentary time has no statistically significance on knee joint pain. And walking (moderate, high) has been shown to reduce the risk of knee joint pain. Conclusion: The results confirmed that walking time had a positive effect on the prevalence of knee joint pain. However, individuals with moderate-intensity walking time and those with high-intensity walking time had different effects on preventing knee joint pain.